Mitral valve nonbacterial thrombotic endocarditis: a rare multi-surgery-tolerant survivor of Trousseau’s syndrome - Yoshiharu Soga; Kaoru Taira; Akira Sugimoto; Manabu Kurosawa; Hiromasa Kira; Takamitsu Su; Kazuhiko Doi; Akira Nakano; Yoshihiro Himura (Surgical Case Reports)
Abstract Background Few previous reports have documented cases of nonbacterial thrombotic endocarditis associated with Trousseau’s syndrome for which surgery proved possible for both the primary tumor and the cardiac lesion. The effectiveness of direct oral anticoagulants in patients with Trousseau’s syndrome has also received scant attention. Case presentation A 69-year-old man with repeated episodes of cerebral infarction was diagnosed as having nonbacterial thrombotic endocarditis after mitral valve replacement surgery. Stroke recurred preoperatively under apixaban administration. A stomach biopsy also identified gastric adenocarcinoma, and gastric surgery was performed on the 40th postoperative day. The patient was discharged from the hospital and has been free of thromboembolism under a regime of subcutaneous heparin self-injection thereafter. Conclusions We have reported a rare multi-surgery-tolerant survivor of Trousseau’s syndrome in whom subcutaneous heparin injection was useful for preventing thromboembolic events over a long period.